Preliminary Safety and Efficacy of Proton Plus Carbon-Ion Radiotherapy With Concurrent Chemotherapy in Limited-Stage Small Cell Lung Cancer - Ma, Ning-Yi; Chen, Jian; Ming, Xue; Jiang, Guo-Liang; Lu, Jiade J.; Wu, Kai-Liang; Mao, Jingfang (Frontiers in Oncology, 2021)
Objectives: This study aimed to investigate the tolerance and effect of proton plus carbon ion radiotherapy with concurrent chemotherapy, in limited-stage small cell lung cancer using the pencil beam scanning technique. Materials and Methods: From March 2017 to April 2020, 25 patients with limited-stage small cell lung cancer treated with combined proton and carbon-ion radiotherapy were analyzed. The primary lesions and involved lymph nodes were irradiated using 2–4 portals. Proton and sequential carbon-ion beams were delivered with a median dose of 67.1 (range, 63–74.8) GyE as fraction doses of 2.0–2.2 GyE with proton beams in 20–23 fractions, and 3.0–3.8 GyE with carbon ions in 5–8 fractions. Chemotherapy was delivered concurrently with radiotherapy in all patients. Results: At the last follow-up, the 2-year overall and locoregional progression-free survival rates were 81.7% and 66.7%, respectively. Radiochemotherapy was well tolerated, with grade 1, 2, and 3 acute toxicities occurring in 12.0%, 68.0%, and 20.0% of patients, respectively. All grade 3 acute toxicities were hematologically-related changes. One patient experienced grade 3 acute non-hematological toxicity in the esophagus, and one other patient had grade 3 bronchial obstruction accompanied by obstructive atelectasis as a late side effect. Conclusion: Proton plus carbon-ion radiotherapy using pencil beam scanning yielded promising survival rates and tolerability in patients with limited-stage small cell lung cancer. A prospective clinical study is warranted to validate the therapeutic efficacy of particle radiotherapy in combination with chemotherapy in limited-stage small cell lung cancer.